Composite cathode material, preparation method thereof, cathode and battery

CN120987379BActive Publication Date: 2026-10-16BEIQI FOTON MOTOR CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510888019.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2026-10-16
Estimated Expiration
2045-06-27

AI Technical Summary

Technical Problem

申请号为201410193632.4公布了一种锆酸锂包覆的锂离子电池富锂正极材料及其制备方法,以 0.4Li2MnO3·0.6LiNi1/3Co1/3Mn1/3O2作为复合粒子的内核,并以Li2ZrO3作为富锂正极材料的复合粒子的外壳,该技术在制备Li2ZrO3过程中需要添加过量的锂盐,过量的锂盐会导致材料表面残锂较多,较多的残锂会与痕量的水和二氧化碳发生副反应导致材料的首效及循环性能变差

Benefits of technology

[0016] Through the above technical solution, this disclosure involves a hydrothermal reaction of layered oxide particles, a zirconium source, and an organic acid ligand in an organic solvent to generate a porous zirconium complex (Zr-MOF) coating the surface of the layered oxide particles. The hydrothermal reaction product is then mixed with a lithium source and sintered to form a porous Li₂ZrO₃ coating layer in situ. This method allows for better control of the coating amount, preventing agglomeration and ensuring more uniform coating on the surface of the layered oxide particles. Furthermore, the in-situ formation of a porous coating layer effectively reduces excess residual alkali on the cathode surface, improves the stability of the coating layer, and facilitates lithium ion migration, further enhancing the initial coulombic efficiency and rate performance of the composite cathode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120987379B_ABST
    Figure CN120987379B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a composite positive electrode material and a preparation method, a positive electrode and a battery, the method comprising: (1) contacting layered oxide particles, a zirconium source, an organic acid ligand and an organic solvent to perform a hydrothermal reaction to obtain a solid product after the hydrothermal reaction; (2) mixing the solid product with a lithium source and then performing a sintering treatment. The method of the present disclosure can better control the coating amount of the coating layer, so that the coating layer is not prone to agglomeration, and the in-situ formation of the porous coating layer can effectively reduce the excessive residual alkali on the surface of the positive electrode, improve the stability of the coating layer, and be more conducive to the migration of lithium ions, further improving the initial coulomb efficiency and rate performance of the composite positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of battery technology, specifically to a composite cathode material and its preparation method, as well as a cathode and a battery. Background Technology

[0002] Layered oxide cathode materials for lithium-ion batteries possess characteristics such as high specific capacity and high operating voltage, making them the most widely used cathode materials in the commercialization of the new energy industry. However, layered oxide materials suffer from drawbacks such as low first-cycle coulombic efficiency and poor rate performance.

[0003] In the prior art, application number 201911057819.0 discloses a ternary material LiNi for lithium batteries. 0.8 Co 0.1 Mn 0.1 A method for coating Li2ZrO3 onto the surface of O2 involves a wet chemical passivation coating of Li2ZrO3 onto the surface of a ternary cathode material for lithium-ion batteries. This technique uses a wet coating method to form a relatively dense Li2ZrO3 on the surface of the cathode material. Application number 201410193632.4 discloses a lithium-rich cathode material for lithium-ion batteries coated with lithium zirconate and its preparation method, using 0.4Li2MnO3·0.6LiNi... 1 / 3 Co 1 / 3 Mn 1 / 3 Using O2 as the core of the composite particles and Li2ZrO3 as the shell of the lithium-rich cathode material, this technology requires the addition of excessive lithium salt during the preparation of Li2ZrO3. Excessive lithium salt will result in more residual lithium on the material surface. The excessive residual lithium will react with trace amounts of water and carbon dioxide, leading to a deterioration in the material's first-efficiency and cycle performance.

[0004] Current technologies mainly modify materials through surface coating and bulk doping. However, current coating methods are difficult to achieve uniform coating. Although oxides and phosphates used for coating have good structural stability, they have low electrical conductivity, which can easily lead to further deterioration of the material's rate performance after coating. Summary of the Invention

[0005] The purpose of this disclosure is to provide a composite cathode material and its preparation method, a cathode and a battery. This method can better control the coating amount, making the coating layer less prone to agglomeration. In-situ formation of a porous coating layer can effectively reduce excessive residual alkali on the cathode surface, improve the stability of the coating layer, and facilitate the migration of lithium ions, thereby further improving the first coulombic efficiency and rate performance of the composite cathode material.

[0006] To achieve the above objectives, the first aspect of this disclosure provides a method for preparing a composite cathode material, the method comprising: (1) The layered oxide particles, zirconium source, organic acid ligand and organic solvent are brought into contact and subjected to hydrothermal reaction to obtain the solid product after hydrothermal reaction; (2) The solid product is mixed with a lithium source and then sintered.

[0007] Optionally, in step (1), the layered oxide particles have Li x Mn y Ni z M 1-y-z O2 represents the chemical formula, where M includes one or more of the following: Co, Al, Zn, Mn, Ti, Zr, Cr, Mg, Ca, La, Fe, Nb, K, Si, V, P, and B; 1 <x<2,0.5<y<1,0≤z<0.5,0≤1-y-z<0.5; The zirconium source is a soluble zirconium salt, which includes one or more of zirconium sulfate, zirconium nitrate, zirconium oxalate, zirconium acetate, zirconium carbonate, or zirconium chloride. The organic acid ligand comprises an organic acid, optionally comprising one or more of formic acid, acetic acid, terephthalic acid, terephthalic acid, pyromellitic acid, 1,2,4-trimethylbenzoic acid, 2,4,6-trimethylbenzoic acid, pyromellitic acid, o-methylbenzoic acid, m-methylbenzoic acid, p-methylbenzoic acid, o-methylphenylacetic acid, m-methylphenylacetic acid, p-methylphenylacetic acid, benzoic acid, and phenylacetic acid. The organic solvent includes one or more of N,N-dimethylformamide, ethanol, methanol, acetone, diethyl ether, chloroform, acetonitrile, acrylonitrile, and dichloromethane.

[0008] Optionally, in step (1), the molar ratio of the zirconium source to the organic acid ligand is 1:(0.2~3).

[0009] Optionally, in step (1), the conditions for the hydrothermal reaction include: a temperature of 60~200℃ and a time of 10~120h.

[0010] Optionally, the method further includes: in step (1), an auxiliary agent is added to the hydrothermal reaction system, the auxiliary agent including an inorganic base, the inorganic base including sodium hydroxide; The molar ratio of the organic acid ligand to the inorganic base is 1:(2~8).

[0011] Optionally, step (1) includes: dissolving the zirconium source in the organic solvent to form a first mixed solution; and dissolving the organic acid ligand and the auxiliary agent in the organic solvent to form a second mixed solution; The layered oxide particles, the first mixed solution, and the second mixed solution are brought into contact to carry out the hydrothermal reaction.

[0012] Optionally, in step (2), the lithium source includes a soluble lithium compound, which includes one or more of lithium sulfate, lithium nitrate, lithium acetate, lithium chloride, lithium carbonate, lithium hydroxide, and lithium oxalate. The molar ratio of the zirconium complex to the lithium source in the solid product is 1:(0.5~2.5). The sintering conditions include: a temperature of 200~700℃ and a time of 5~20h.

[0013] The second aspect of this disclosure provides a composite cathode material prepared using the method described in the first aspect of this disclosure. The composite cathode material includes layered oxide particles and a coating layer covering the surface of the layered oxide particles. The coating layer includes Li2ZrO3. The thickness of the coating layer is 30~100 nm.

[0014] A third aspect of this disclosure provides a positive electrode, including the composite positive electrode material described in the second aspect of this disclosure.

[0015] This disclosure provides a fourth aspect of a battery, including the positive electrode described in the third aspect of this disclosure.

[0016] Through the above technical solution, this disclosure involves a hydrothermal reaction of layered oxide particles, a zirconium source, and an organic acid ligand in an organic solvent to generate a porous zirconium complex (Zr-MOF) coating the surface of the layered oxide particles. The hydrothermal reaction product is then mixed with a lithium source and sintered to form a porous Li₂ZrO₃ coating layer in situ. This method allows for better control of the coating amount, preventing agglomeration and ensuring more uniform coating on the surface of the layered oxide particles. Furthermore, the in-situ formation of a porous coating layer effectively reduces excess residual alkali on the cathode surface, improves the stability of the coating layer, and facilitates lithium ion migration, further enhancing the initial coulombic efficiency and rate performance of the composite cathode material.

[0017] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description

[0018] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings: Figure 1 This is an SEM image of the layered oxide particles of Embodiment 1 of this disclosure.

[0019] Figure 2 This is a SEM image of the composite cathode material obtained in Embodiment 1 of this disclosure. Detailed Implementation

[0020] Hereinafter, specific embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not intended to limit the present disclosure.

[0021] In a first aspect, the present disclosure provides a method for preparing a composite positive electrode material, the method comprising: (1) bringing layered oxide particles, a zirconium source, an organic acid ligand and an organic solvent into contact to carry out a hydrothermal reaction, so as to obtain a solid product after the hydrothermal reaction; (2) mixing the solid product with a lithium source, followed by sintering treatment.

[0022] In the present disclosure, a porous zirconium complex (Zr-MOF) is generated and coated on the surface of the layered oxide particles by subjecting the layered oxide particles, the zirconium source and the organic acid ligand to a hydrothermal reaction in an organic solvent; the product of the hydrothermal reaction is mixed with the lithium source and then sintered, so that the porous Zr-MOF in-situ forms a porous Li₂ZrO₃ coating layer. The method of the present disclosure can better control the coating amount of the coating layer, make the coating layer less prone to agglomeration, and can coat the surface of the layered oxide particles more uniformly. Moreover, the porous coating layer formed in-situ can effectively reduce the excess residual alkali on the surface of the positive electrode, improve the stability of the coating layer, and is more conducive to the migration of lithium ions, further improving the initial Coulombic efficiency and rate performance of the composite positive electrode material.

[0023] According to an embodiment of the present disclosure, in step (1), the layered oxide particles have Li x Mn y Ni z M 1-y- z O₂ represented chemical formula, M includes one or more of Co, Al, Zn, Mn, Ti, Zr, Cr, Mg, Ca, La, Fe, Nb, K, Si, V, P and B; 1<x<2, 0.5<y<1, 0≤z<0.5, 0≤1-y-z<0.5.

[0024] The present disclosure does not specifically limit the preparation method of the layered oxide particles, which may be a conventional method in the art, for example, the layered oxide particles are prepared by the following method: (a) according to the proportion of each metal in the required layered oxide particles, a soluble nickel salt, a soluble metal salt M and a soluble manganese salt are synthesized by a co-precipitation method to obtain Mn y Ni z M 1-y-z (OH)₂ or Mn y Ni z M 1-y-z CO₃ precursor, 0.5<y<1, 0≤z<0.5, 0≤1-y-z<0.5; and the Mn y Ni z Co1-y-z (OH)2 or Mn y Ni z Co 1-y-z (a) The CO3 precursor was filtered, washed, and dried to obtain an intermediate product; (b) The intermediate product was mixed with lithium salt at a molar ratio of 1:1 to 1:2, and the mixed solid was sintered at 500 to 1000°C for 5 to 20 hours to finally obtain layered oxide particles Li. x Mn y Ni z M 1-y-z O2, M includes one or more of Co, Al, Zn, Mn, Ti, Zr, Cr, Mg, Ca, La, Fe, Nb, K, Si, V, P, and B; 1 <x<2,0.5<y<1,0≤z<0.5,0≤1-y-z<0.5。

[0025] According to one embodiment of this disclosure, the soluble manganese salt may include one or more of manganese sulfate, manganese nitrate, manganese oxalate, manganese acetate, and manganese chloride; the soluble nickel salt may include one or more of nickel sulfate, nickel nitrate, nickel oxalate, nickel acetate, and nickel chloride; and the soluble metal salt M is one or more of sulfuric acid M, nitric acid M, oxalic acid M, acetic acid M, and chloride M.

[0026] According to one embodiment of this disclosure, in step (1), the zirconium source includes a soluble zirconium salt, which may include one or more of zirconium sulfate, zirconium nitrate, zirconium oxalate, zirconium acetate, zirconium carbonate, or zirconium chloride.

[0027] According to one embodiment of this disclosure, in step (1), the organic acid ligand comprises an organic acid. Optionally, the organic acid includes one or more of formic acid, acetic acid, terephthalic acid, terephthalic acid, pyromellitic acid, 1,2,4-trimethylbenzoic acid, 2,4,6-trimethylbenzoic acid, pyromellitic acid, o-methylbenzoic acid, m-methylbenzoic acid, p-methylbenzoic acid, o-methylphenylacetic acid, m-methylphenylacetic acid, p-methylphenylacetic acid, benzoic acid, and phenylacetic acid. In the above embodiment, the organic acid can be better dissolved in organic solvents, which is beneficial for forming Zr-MOF with the zirconium source.

[0028] According to one embodiment of this disclosure, in step (1), the organic solvent includes one or more of N,N-dimethylformamide, ethanol, methanol, acetone, diethyl ether, chloroform, acetonitrile, acrylonitrile, and dichloromethane.

[0029] According to one embodiment of this disclosure, in step (1), the molar ratio of the zirconium source to the organic acid ligand is 1:(0.2~3), for example, it can be any value within the range of 1:0.2, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, or any combination thereof. The above embodiment is advantageous for forming Zr-MOFs with suitable structures.

[0030] According to one embodiment of this disclosure, in step (1), the conditions for the hydrothermal reaction include: a temperature of 60~200℃, for example, any value within the range of 60℃, 70℃, 80℃, 90℃, 100℃, 130℃, 150℃, 170℃, 200℃, or any combination thereof; and a time of 10~120h, for example, any value within the range of 10h, 20h, 30h, 40h, 50h, 60h, 70h, 80h, 90h, 100h, 110h, 120h, or any combination thereof. The above embodiment facilitates the formation of a suitable Zr-MOF structure between the organic acid and the zirconium source, facilitates a more uniform coating of Zr-MOF on the surface of layered oxide particles, and further facilitates the formation of a porous Li2ZrO3 coating layer.

[0031] According to one embodiment of this disclosure, the method further includes: in step (1), an auxiliary agent is added to the hydrothermal reaction system, the auxiliary agent comprising an inorganic base, the inorganic base comprising sodium hydroxide; the molar ratio of the organic acid ligand to the inorganic base is 1:(2~8), for example, it can be any value within the range of 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or any combination thereof. In the above embodiment, the use of an inorganic base auxiliary agent can neutralize part of the excess organic acid ligand, making the formed Zr-MOF intermediate more stable.

[0032] According to one embodiment of this disclosure, step (1) includes: dissolving the zirconium source in the organic solvent to form a first mixed solution; dissolving the organic acid ligand and the auxiliary agent in the organic solvent to form a second mixed solution; and contacting the layered oxide particles, the first mixed solution, and the second mixed solution to carry out the hydrothermal reaction. The above embodiment facilitates the uniform dispersion of the zirconium source and the organic acid ligand on the surface of the layered oxide particles, resulting in a uniform Zr-MOF coating on the surface of the layered oxide particles.

[0033] According to one embodiment of this disclosure, in step (2), the lithium source includes a soluble lithium compound, which includes one or more of lithium sulfate, lithium nitrate, lithium acetate, lithium chloride, lithium carbonate, lithium hydroxide, and lithium oxalate. This embodiment facilitates the in-situ formation of a porous Li2ZrO3 coating layer on the surface of layered oxide particles using a lithium source-assisted Zr-MOF, resulting in higher ionic conductivity and improved rate performance and first-cycle coulombic efficiency of the composite cathode material.

[0034] According to one embodiment of this disclosure, in step (2), the molar ratio of the zirconium complex (Zr-MOF) to the lithium source in the solid product is 1:(0.5~2.5), for example, it can be any value within the range of 1:0.5, 1:0.7, 1:0.9, 1:1, 1:1.5, 1:2, 1:2.5, or any combination thereof. In this disclosure, the molar amount of the zirconium complex in the solid product = m (Zr-MOF) / M (Zr-MOF) , where m (Zr-MOF) M represents the mass difference between the solid product and the layered oxide particles. (Zr-MOF) The value represents the relative molecular weight of Zr-MOF, and its molecular formula was calculated after elemental analysis. The above implementation method facilitates the in-situ formation of a porous coating layer, reduces excess residual alkali on the cathode surface, improves the stability of the coating layer, and further enhances the initial coulombic efficiency and rate performance of the composite cathode material.

[0035] According to one embodiment of this disclosure, in step (2), the sintering conditions include: a temperature of 200~700℃, for example, any value within the range of 200℃, 300℃, 400℃, 500℃, 600℃, 700℃, or any combination thereof; and a time of 5~20h, for example, any value within the range of 5h, 7h, 9h, 10h, 13h, 15h, 17h, 19h, 20h, or any combination thereof. This embodiment facilitates the in-situ formation of a porous Li2ZrO3 coating layer on the surface of layered oxide particles using lithium source-assisted Zr-MOF, resulting in higher ionic conductivity and improving the rate performance and first-cycle coulombic efficiency of the composite cathode material.

[0036] The second aspect of this disclosure provides a composite cathode material prepared using the method described in the first aspect of this disclosure.

[0037] According to one embodiment of this disclosure, the composite cathode material comprises layered oxide particles and a coating layer covering the surface of the layered oxide particles, the coating layer comprising Li₂ZrO₃; the thickness of the coating layer is 30~100 nm, for example, it can be any value within the range of 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or any combination thereof. The above embodiment is beneficial for improving the rate performance and first-cycle coulombic efficiency of the composite cathode material.

[0038] A third aspect of this disclosure provides a positive electrode, including the composite positive electrode material described in the second aspect of this disclosure.

[0039] This disclosure provides a fourth aspect of a battery, including the positive electrode described in the third aspect of this disclosure.

[0040] The present disclosure will be described in detail below with reference to the embodiments, but it is not limited to the present disclosure.

[0041] Example 1 Cobalt (CoSO4), nickel (NiSO4), and manganese (MnSO4) were dissolved in 50 mL of water at a molar ratio of 1:1:4 to obtain a total molar concentration of 2 mol / L, resulting in a mixed metal ion solution. 50 mL of a 10 mol / L NaOH solution and a 1 mol / L ammonia solution were prepared and continuously pumped into the reaction vessel using a peristaltic pump. The reaction was stirred, and the pH was controlled between 11 and 11.4, while the reaction temperature was maintained between 45 and 60 °C. After 12 hours, the mixture was filtered, washed four times, filtered again, and dried to obtain the hydroxide precursor, with the molecular formula MnSO4. 4 / 6 Ni 1 / 6 Co 1 / 6 (OH)2; the precursor of hydroxide Mn 4 / 6 Ni 1 / 6Co 1 / 6 (OH)₂ and lithium carbonate were weighed at a molar ratio of 1:1.65. After weighing, Mn was... 4 / 6 Ni 1 / 6 Co 1 / 6 (OH)₂ and lithium carbonate were stirred and mixed thoroughly. After thorough mixing, the mixture was transferred to a muffle furnace and sintered at 900℃ for 10 hours, with compressed air circulating during the sintering process. After sintering, layered oxide particles of Li₂ were obtained. 1.2 Mn 0.54 Ni 0.13 Co 0.33 O2, SEM characterization as follows Figure 1 As shown.

[0042] (1) Dissolve 5 mmol of ZrCl4 in 50 ml of acetic acid solution to form a first mixed solution. Dissolve 3 mmol of 1,3,5-benzoic acid and 10 mmol of sodium hydroxide in 50 ml of N,N-dimethylformamide (DMF) to form a second mixed solution. The prepared layered oxide particles Li 1.2 Mn 0.54 Ni 0.13 Co 0.33 O2, the first mixed solution, and the second mixed solution were mixed and stirred for 30 minutes. After stirring, the mixture was transferred to a reaction vessel. The reaction temperature was 120°C and the reaction time was 10 hours. After the reaction was completed, the mixture was filtered, washed, dried, and weighed. The molar ratio of zirconium source to organic acid ligand was 1:0.6, and the molar ratio of organic acid ligand to inorganic base was 1:3.33. (2) Subtract the Li content of the layered oxide particles from the mass of the dried and weighed solid. 1.2 Mn 0.54 Ni 0.13 Co 0.33 The mass of O2 was used to calculate the molar amount of Zr-MOF after determining its molecular formula. Zr-MOF and lithium carbonate in the solid product were weighed and mixed at a molar ratio of 1:2. After homogeneous mixing, the mixture was transferred to a muffle furnace for heat treatment at 500℃ for 5 hours. After sintering, a composite cathode material was obtained, consisting of layered oxide particles coated with Li₂ZrO₃, denoted as Li₂ZrO₃@Li 1.2 Mn 0.54 Ni 0.13 Co 0.33 O2; SEM test image as follows Figure 2 As shown, Li2ZrO3 is coated on the surface of layered oxide particles, and the coating thickness is measured to be 55 nm by TEM.

[0043] Example 2 Nickel salt NiSO4, cobalt salt CoSO4, and manganese salt MnSO4 were dissolved in 50 mL of water at a molar ratio of 8:1:1 to obtain a total molar concentration of 2 mol / L, resulting in a mixed metal ion solution. 50 mL of a 10 mol / L NaOH solution and a 1 mol / L ammonia solution were prepared and continuously pumped into the reaction vessel using a peristaltic pump. The reaction was stirred, and the pH was controlled at 11–11.4, while the reaction temperature was maintained at 45–60 °C. After 12 hours, the mixture was filtered, washed four times, filtered again, and dried to obtain the hydroxide precursor. The molecular formula of the hydroxide precursor is MnSO4. 0.8 Ni 0.1 Co 0.1 (OH)2. Mn 0.8 Ni 0.1 Co 0.1(OH)₂ and lithium hydroxide were weighed at a molar ratio of 1:1.05. After weighing, Mn... 0.8 Ni 0.1 Co 0.1 (OH)₂ and lithium hydroxide were stirred and mixed thoroughly. After thorough mixing, the mixture was transferred to an atmosphere furnace and sintered at 800℃ for 10 hours, with pure oxygen purging throughout the process. After sintering, layered oxide particles of LiMn were obtained. 0.8 Ni 0.1 Co 0.1 O2.

[0044] (1) Dissolve 5 mmol of ZrCl4 in 50 ml of acetic acid solution to form the first mixed solution, and dissolve 3 mmol of terephthalic acid and 10 mmol of sodium hydroxide in 50 ml of DMF to form the second mixed solution; then prepare LiMn 0.8 Ni 0.1 Co 0.1 O2, the first mixed solution, and the second mixed solution were mixed and stirred for 30 min. After stirring, the mixture was transferred to a stainless steel reactor, and the reaction temperature was 120℃ for 10 h. After the reaction, the mixture was filtered, washed, dried, and the solid product was weighed. The molar ratio of zirconium source to organic acid ligand was 1:0.6, and the molar ratio of organic acid ligand to inorganic base was 1:3.33. (2) Subtract the mass of the layered oxide particles LiMn from the mass of the dried and weighed solid. 0.8 Ni 0.1 Co 0.1 The mass of O2 was used to calculate the molar amount of Zr-MOF after determining its molecular formula. O2 was then weighed and mixed with lithium hydroxide at a molar ratio of 1:2. After thorough mixing, the mixture was transferred to a muffle furnace for heat treatment at 500℃ for 5 hours. The resulting composite cathode material, denoted as Li2ZrO3@LiMn, was obtained after sintering. 0.8 Ni 0.1 Co 0.1 O2. The thickness of the Li2ZrO3 coating layer was measured to be 48 nm by TEM.

[0045] Example 3 The method in this embodiment is the same as that in embodiment 1, except that the molar ratio of zirconium source to organic acid ligand in step (1) is 1:0.1.

[0046] Example 4 The method in this embodiment is the same as that in embodiment 1, except that the molar ratio of zirconium source to organic acid ligand in step (1) is 1:5.

[0047] Example 5 The method in this embodiment is the same as that in embodiment 1, except that the conditions for the hydrothermal reaction in step (1) include: a temperature of 50°C and a time of 130h.

[0048] Example 6 The method in this embodiment is the same as that in embodiment 1, except that inorganic alkali sodium hydroxide is not added in step (1).

[0049] Example 7 The method in this embodiment is the same as that in embodiment 1, except that the molar ratio of Zr-MOF to lithium carbonate in the solid product in step (2) is 1:0.1.

[0050] Comparative Example 1 The cathode material of Comparative Example 1 is the layered oxide particles Li from Example 1. 1.2 Mn 0.54 Ni 0.13 Co 0.33 O2.

[0051] Comparative Example 2 The cathode material of Comparative Example 2 is the layered oxide particles LiMn from Example 2. 0.8 Ni 0.1 Co 0.1 O2.

[0052] Test Example 1 The cathode materials obtained in the above embodiments and comparative examples were used to prepare cathodes, and they were assembled into batteries for rate performance testing.

[0053] The battery preparation method includes: weighing 1.8g of the composite positive electrode material obtained in the above examples and the positive electrode material of the comparative example, adding 0.1g of acetylene black as a conductive agent, 4ml of N-methylpyrrolidone (NMP) as a solvent, and 5130-PVDF as a binder, mixing in a homogenizer, forming a slurry, uniformly coating it on aluminum foil, forming a sheet, and drying it in a vacuum oven at 80℃ for 12h to obtain an electrode sheet, which is then placed in a glove box. Using this electrode sheet as the working electrode, lithium metal as the counter electrode, Celgard 2400 as the separator, and 1mol / L LiPF6 / EC:DEC:DMC (volume ratio 1:1:1) as the electrolyte, a CR2016 coin cell is assembled.

[0054] Performance testing method: Constant current charge-discharge tests were conducted at room temperature. The test voltage range for the first three weeks was 2V~4.8V, and the test voltage range for rate performance was 2V~4.6V. Charge-discharge rates of 0.2C, 0.5C, 1.0C, 2.0C, and 5.0C were performed 10 times each. The initial charge specific capacity at each rate was measured, and the coulombic efficiency (first-time efficiency) during the first charge-discharge process at 0.2C was recorded. The test results are shown in Table 1. Table 1

[0055] According to the data in Table 1, the composite cathode material disclosed herein has an in-situ generated porous coating layer, and the resulting composite cathode material has a certain porosity, which can improve the first-cycle coulombic efficiency and rate performance of the composite cathode material.

[0056] Compared to Comparative Example 1, the composite cathode material used in Example 1 has an in-situ generated porous coating layer with a certain porosity, which is conducive to the migration of lithium ions. The composite cathode material has higher first-cycle coulombic efficiency and rate performance.

[0057] Compared to Comparative Example 2, the composite cathode material used in Example 2 has an in-situ generated porous coating layer with a certain porosity, which is conducive to the migration of lithium ions. The composite cathode material has higher first-cycle coulombic efficiency and rate performance.

[0058] By comparing Examples 1 and 3, it can be seen that the molar ratio of zirconium source to organic acid ligand in Example 1 is within the preferred range of this disclosure, which is conducive to the formation of a suitable Zr-MOF structure, and further improves the first-efficiency and rate performance of the prepared composite cathode material.

[0059] By comparing Examples 1 and 4, it can be seen that the molar ratio of zirconium source to organic acid ligand in Example 1 is within the preferred range of this disclosure, which is conducive to the formation of a suitable Zr-MOF structure and the generated Zr-MOF is more stable, further improving the first-efficiency and rate performance of the prepared composite cathode material.

[0060] By comparing Examples 1 and 5, it can be seen that Example 1, under the preferred hydrothermal reaction conditions of this disclosure, is conducive to the formation of a suitable Zr-MOF structure, which is beneficial to the more uniform coating of Zr-MOF on the surface of layered oxide particles, and further improves the first efficiency and rate performance of the prepared composite cathode material.

[0061] By comparing Examples 1 and 6, it can be seen that the addition of an additive to the hydrothermal reaction system in Example 1 makes the formed Zr-MOF intermediate product more stable, and further improves the first efficiency and rate performance of the prepared composite cathode material.

[0062] By comparing Examples 1 and 7, it can be seen that the molar ratio of zirconium complex to lithium source in the solid product of Example 1 is within the preferred range of this disclosure, which is conducive to the in-situ formation of a porous coating layer, reduces the excess residual alkali on the cathode surface, improves the stability of the coating layer, and further makes the first efficiency and rate performance of the prepared composite cathode material higher.

[0063] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0064] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0065] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A method for preparing composite cathode materials, characterized in that, The method includes: (1) The layered oxide particles, zirconium source, organic acid ligand and organic solvent are brought into contact and subjected to hydrothermal reaction to obtain the solid product after hydrothermal reaction; (2) The solid product is mixed with a lithium source and then sintered; The layered oxide particles contain Li x Mn y Ni z M 1-y-z O2 represents the chemical formula, where M includes one or more of the following: Co, Al, Zn, Mn, Ti, Zr, Cr, Mg, Ca, La, Fe, Nb, K, Si, V, P, and B; 1 <x<2,0.5<y<1,0≤z<0.5,0≤1-y-z<0.5; The zirconium source is a soluble zirconium salt, which includes one or more of zirconium sulfate, zirconium nitrate, zirconium oxalate, zirconium acetate, zirconium carbonate, or zirconium chloride. The organic acid ligand comprises an organic acid, which includes one or more of formic acid, acetic acid, terephthalic acid, terephthalic acid, pyromellitic acid, 1,2,4-trimethylbenzoic acid, 2,4,6-trimethylbenzoic acid, pyromellitic acid, o-methylbenzoic acid, m-methylbenzoic acid, p-methylbenzoic acid, o-methylphenylacetic acid, m-methylphenylacetic acid, p-methylphenylacetic acid, benzoic acid, and phenylacetic acid. The organic solvent includes one or more of N,N-dimethylformamide, ethanol, methanol, acetone, diethyl ether, chloroform, acetonitrile, acrylonitrile, and dichloromethane; The molar ratio of the zirconium source to the organic acid ligand is 1:(0.2~3). The conditions for the hydrothermal reaction include: a temperature of 60~200℃; and a time of 10~120h. The lithium source includes a soluble lithium compound, which includes one or more of lithium sulfate, lithium nitrate, lithium acetate, lithium chloride, lithium carbonate, lithium hydroxide, and lithium oxalate. The molar ratio of the zirconium complex to the lithium source in the solid product is 1:(0.5~2.5). The sintering conditions include: a temperature of 200~700℃ and a time of 5~20h.

2. The method for preparing composite cathode materials according to claim 1, wherein, The method further includes: in step (1), an auxiliary agent is added to the hydrothermal reaction system, the auxiliary agent including an inorganic base, the inorganic base including sodium hydroxide; The molar ratio of the organic acid ligand to the inorganic base is 1:(2~8).

3. The method for preparing composite cathode materials according to claim 2, wherein, Step (1) includes: dissolving the zirconium source in the organic solvent to form a first mixed solution; and dissolving the organic acid ligand and the auxiliary agent in the organic solvent to form a second mixed solution. The layered oxide particles, the first mixed solution, and the second mixed solution are brought into contact to carry out the hydrothermal reaction.

4. The composite cathode material prepared by the method for preparing composite cathode materials according to any one of claims 1 to 3, wherein, The composite cathode material includes layered oxide particles and a coating layer covering the surface of the layered oxide particles, wherein the coating layer includes Li2ZrO3; The thickness of the coating layer is 30~100nm.

5. A positive electrode, characterized in that, Including the composite cathode material as described in claim 4.

6. A battery, characterized in that, Includes the positive electrode as described in claim 5.

Citation Information

Patent Citations

  • Lithium zirconate-cladded lithium-rich positive material for lithium ion battery and preparation method thereof

    CN103996838A

  • Method for coating surface of lithium battery ternary material LiNi0.8Co0.1Mn0.1O2 with Li2ZrO3

    CN110649252A

  • Zirconium-based MOF material-based zirconium oxide-coated lithium ion battery ternary positive electrode material and preparation method thereof

    CN109950518A

  • Lithium lanthanum zirconate-coated modified positive electrode material, preparation method thereof and lithium ion battery

    CN116779871A